1988
DOI: 10.3177/jnsv.34.195
|View full text |Cite
|
Sign up to set email alerts
|

The bioavailability of calcium in spinach and calcium-oxalate to calcium-deficient rats.

Abstract: SummaryWe estimated the utilization of calcium in spinach and calcium-oxalate to calcium-deficient rats, and the effect of oxalic acid on absorption of dietary calcium by using calcium-deficient rats. The body weight gain of the calcium-deficient rats for 8 days receiving a calcium deficient diet supplemented with raw-powdered spinach (R-sp), boiled powdered spinach (B-sp), or calcium-oxalate (Ca-ox), and a control diet supplemented with oxalic acid (OX-C) were 4.8, 2.8, 4.9, and 5.1g, respectively. The calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Kim and Zemel (1986) found spinach calcium much less soluble than skim milk calcium. Poor bioavailability of calcium from spinach has been confirmed in humans (Heaney et al, 1988) and rats (Kikunaga et al, 1988). This was attributed to formation of insoluble calcium oxalate.…”
Section: Introductionmentioning
confidence: 92%
“…Kim and Zemel (1986) found spinach calcium much less soluble than skim milk calcium. Poor bioavailability of calcium from spinach has been confirmed in humans (Heaney et al, 1988) and rats (Kikunaga et al, 1988). This was attributed to formation of insoluble calcium oxalate.…”
Section: Introductionmentioning
confidence: 92%
“…For this reason, individuals with already existing and untreated kidney or gallbladder problems may want to avoid eating eggplant [236,237]. Laboratory studies have shown that oxalates may also interfere with absorption of calcium from the body [238].…”
Section: Eggplantmentioning
confidence: 99%
“…It is possible that the low body weight of the Ox-C rats resulted from an apparent absoption and retention of calcium which is the lowest among the dietary groups. It is known that Ox-C impairs calcium absorption (12,13). There is a possibility that this phenomenon observed among the Ox-C rats might have resulted from disturbed calcium absorption by Ox-C.…”
Section: Discussionmentioning
confidence: 96%
“…calcium (12,13) and other minerals. We have already reported that the oxalic acid concentration in spinach was the highest of those vegetables analyzed, and that the calcium absorption ratio by rats from spinach was lower than that from calcium oxalate (14).…”
Section: Discussionmentioning
confidence: 99%